Ahmad Al-Sirhindi's Stations of Muraqabah in the Naqshabandi Order Taught by Wan Sulaiman Wan Siddik, A 19th Century Malay Scholar in the Malay World - Muhammad Khairi Mahyuddin; Zakaria Stapa; Faudzinaim Badaruddi (Center For Promoting Ideas, USA, 2024)
International Journal of Business and Social Science Vol. 4 No.6; June 2013